Pengaruh Kinerja Karyawan dan Motivasi Kerja Terhadap Kualitas Pelayanan Kesehatan di PUSKESMAS Kedupok Probolinggo - Supriyono Supriyono (Ecobuss, 2016)
Quality services is a central point share services company because will affect customer satisfaction. Customer satisfaction will Appears when quality of service good. Quality divides good service servqual hearts five dimensions, ie; Tangibles (Physical Evidence), Reliability (reliability), Responsiveness (Responsiveness), Assurance (Assurance) and Empathy (Attention what is individual). A company will win the competition when creates value and can be shown to the satisfaction giving customers through the delivery of goods services or because quality and value needs and desires quality services expected by consumers quality it is determined by service. objective want achieved by researchers is: (1) For determine the effect operates simultaneously costs kos employees and motivation employee Against quality health care in health centers Kedupok Probolinggo, (2) For determine the effect operates partial costs kos employees and motivation employee aAgainst quality services health outposts Kedupok Probolinggo, (3) For determine variable costs from boarding and motivation of employees, which of the dominant influence quality in services in health centers Kedupok Probolinggo. Keywords: Performance, Motivation, Quality Health Care